Perbedaan dan Kontribusi Mazhab Fikih dalam Perkembangan Hukum Islam - Vinda Nurul Hidayatul Aiman; Achmad Mukhsin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The diversity of schools of jurisprudence in Islam, such as Hanafi, Maliki, Syafii, Hanbali, and Shia, reflects various legal approaches that develop according to their respective social, cultural and historical contexts. The four Sunni schools of thought have different methodologies, but are still based on the Koran and Hadith. The Hanafi school of thought is known to be flexible in its legal interpretation, while the Maliki school prioritizes the practices of the people of Medina. Syafii stands out for his systematic use of hadith, while Hanbali is more strict in following authentic hadith. The Shia school of thought with its distinctive characteristics also enriches the understanding of Islamic jurisprudence. This diversity shows that Islamic law is dynamic and contextual, allowing adaptation to changes in time and place. Therefore, Muslims need to prioritize tolerance and respect differences. The diversity of sects is not a cause of division, but rather a means of deepening religious understanding and practice. Dialogue between schools of thought is the key to strengthening unity, increasing mutual understanding, and creating harmony in social life.